Students and Lecturers of Kaunas Polytechnic Institute in the KGB Spotlight (1951–1989) - Veilentienė , Audronė (Genocidas ir rezistencija, 2024)
The KGB branch at the Council of Ministers of the Lithuanian SSR paid particular attention to schools of higher education in Kaunas who were supposed to train intelligentsia loyal to the Soviet government. During the interwar period Kaunas was the temporary capital of Lithuania and the majority of schools of higher education in Kaunas stemmed from the Lithuanian University (Vytautas Magnus University) founded in 1922. Therefore, there were a number of representatives of the national intelligentsia in Kaunas who exerted a significant influence on the younger generation. During the Soviet period, the KGB monitored political sentiments, research and foreign relations of lecturers and students of all schools of higher education, including Kaunas Polytechnic Institute (KPI). The KGB carried out the surveillance using a network of trusted people and agents and was assisted in this by functionaries of the Communist Party and the All-Union Leninist Young Communist League (Komsomol). In 1951–1973, the KGB in Lithuania disclosed the underground organisations in which KPI students and teachers were involved. In order to identify anti-Soviet organisations, the KGB agents used provocateurs and later – listening devices. Seeking to “re-educate” KPI students and teachers who were involved in anti-Soviet organisations, the KGB applied typical methods: arrest, courts, detention and forced labour in Soviet labour camps. “Less serious crimes” of students, such as singing of anti-Soviet songs, belonging to a religious group or asking inappropriate questions at ideological sciences lectures, were punished with preventive conversations, public discussions of their behaviour, reprimands, removal from the Komsomol, and expulsion from the Institute. Although the functionaries of the KGB and the Communist Party applied measures aimed at suppressing national consciousness and statehood aspirations and ideological censorship, there were frequent manifestations of dissatisfaction with the Soviet occupation at KPI and some students and lecturers continued to participate in the anti-Soviet resistance. In order to protect young people from the negative influence, the KGB sought to prevent the former deportees or prisoners from studying and working at the schools of higher education. Prof. Kazimieras Baršauskas, Rector of KPI, disobeyed prohibitions by KGB leaders, and the Institute had a number of students who were former deportees and political prisoners. The KGB sought to expand its network of agents at KPI, but their reports indicate that there were too few agents. The KGB tried to use some KPI lecturers who travelled abroad for their sabbatical as their agents at the institute and for technical espionage abroad. In order to control research work related to military orders and trips abroad, the 1st Unit and the Foreign Relations Unit were set up at the institute; these were actually led by KGB officers. The KGB monitored whether the enemies from the capitalist countries were interested in what was developed at KPI laboratories or in researchers who wrote dissertations on the so-called classified topics. In the 1980s, the KGB mainly focused on the KPI Scientific Centre Vibrotechnika, the Ultrasound Laboratory, and faculties of Automation, Radio Electronics, Computer Technology and Mechanical Engineering, the Nemunas song and dance ensemble, tourist society and the society for regional studies.